Simulation on air conditioning using fuzzy logic - Bibi Rubiatul Adawiah, Mustafa Kamal (2012)
Air conditioning systems are integral part of almost every institution.It contributes significant part of total energy consumption.Studies suggest that in locations like class rooms,hall and offices in UMP,air conditioning can contribute as much as 75% of total energy intake.Even in homes and offices,power consumed by air conditioners is significant.Fuzzy logic is actually one of the artificial intelligence techniques that being used widely in development system nowadays.Simulation on Air Conditioner Using Fuzzy Logic is a stand-alone system that enable user to display the simulation of air conditioner spinning fan. This system is made for UMP’s staff or lecturer to simulate how the fan is spin according to the temperature.The system has been successfully developed within time and user can display the output of the percentage of the fan speed based on two inputs that are set temp and current_temp.the simulation is shown based on the inputs and output calculated using Fuzzy Logic technique.